Fatores de risco e prevenção ao feminicídio: análise de dados do formulário nacional de avaliação de risco no município de Alfenas/MG nos anos de 2021 a 2022 à luz da teoria da reprodução social - Franco, Rafaela Santos (2024)
Aiming to contribute to the prevention and combat of serious violence and femicide committed in intimate, domestic, and family contexts against women, researchers, and researchers in Public Security sought to identify risk factors that would lead aggressors to commit such crimes and build scientific instruments to evaluate and manage these risks. However, is it possible to determine the risk of physical violence against women based on these factors? Given this problem, the present research aims to analyze the risk factors for domestic physical violence in a municipality in Minas Gerais (Alfenas-MG) between 2021 and 2022. The study investigated, through Social Reproduction Theory (SRT), 174 Police Reports and 90 Risk Assessment Forms (FONAR) contained therein involving physical violence (bodily injury and attempted femicide) committed against women in the domestic and family context, as well as the management carried out by the Specialized Women's Assistance Police Station. Using statistical treatment, descriptive statistics, and cross-tabulation of data, we analyzed the data using the SRT framework. Crossing the variables age, ethnic/racial identity, and education, the group of women that presented the highest frequency of cases of physical violence were women between 25 and 34 years of age, white, and who had completed high school. The aggressors are mainly men aged between 15 and 33, most of whom are intimate partners of the victims. In 27.8% (n=90) of the cases, the woman stated that she had already registered a police report or had a protective measure against the same aggressor. The data also showed that in 56.7% (n=90) of cases, there was an indication of using the victim's own body. The attacker and his physical strength to punch, kick, push, pull hair, or cause mechanical asphyxiation. In 28% (n=90) of cases, victims have already heard from the aggressor something similar to the phrase: "If you're not mine, you won't be anyone else's." In turn, 34.8% (n=90) of the victims indicated that the aggressor had already practiced other behaviors of excessive jealousy and control that did not appear in the FONAR items. In the predominant age group, black and brown victims are less educated than white victims, and 24.4% (n=90) of the victims considered themselves financially dependent on the aggressors, with 28.89% (n=90) of the aggressors being unemployed. Saturday and Sunday are the days when physical violence occurs most (51%), with the most frequent time (44.8%) being between 6:00 pm and 11:59 pm, which may indicate the need for more patrolling outside business hours (after 6 pm) and on weekends. The results indicate that such risk factors can contribute to identifying demands for the referral of aggressors to the confrontation network. However, they do not explain the roots of physical violence against women in affective relationships or domestic and family environments, nor how to break with these answers that we point out from the SRT.